Daily intake of a bean-fiber fortified bar reduces oxidative stress - Tierrablanca-Vázquez, Irvin E.; Luna-Martínez, Francisco; Guzmán-Maldonado, Salvador H.; Ramírez-Emiliano, Joel; Aguilar-Zavala, Herlinda (Archivos Latinoamericanos de Nutrición (ALAN), 2020)
It has been proposed that the consumption of common beans (Phaseolus vulgaris L.) reduces cardiovascular risk, and prevents and controls both chronic and degenerative diseases. The aim of this study was to compare the antioxidant capacity of a bean-fiber fortified bar (BFB) versus a commercial bar (CB) in 60 Mexican men and women (18-65 years old), who were randomly distributed in two groups: BFB or CB; individuals consumed a bar a day for one month. Anthropometric data, food intake and blood samples were collected. Glucose tolerance (GTT), lipid profile (PL), and lipid peroxidation (TBARS) tests were performed; carbonyls groups in serum oxidized proteins were also measured. GTT and PL were not different between both groups in either the 15 or 30-day follow-up of bar consumption assessments. There were no significant differences in either TBARS or carbonyl concentration between groups; BFB group showed higher levels of serum lipid peroxidation in basal and fifteen days measurements; these levels decreased at the final evaluation: No differences were detected on carbonyl levels between groups. In conclusion, 30 days of fiber bean bar consumption did not alter glucose or PL levels, while, in the BFF group, oxidative stress decreased within 30 days of the consumption of the fortified bar. Se ha propuesto que el consumo de frijol común (Phaseolus vulgaris L.) reduce el riesgo cardiovascular, y previene y controla las enfermedades crónicas y degenerativas. El objetivo del presente estudio fue comparar la capacidad antioxidante de una barra fortificada con fibra de frijol (BFB) versus una barra comercial (CB) en 60 hombres y mujeres mexicanos (18-65 años de edad), quienes aleatoriamente fueron distribuidos en dos grupos: El grupo BFB y el CB que consumieron la barras fortificada con frijol y la barra comercial, respectivamente, durante un mes. Se recopilaron datos antropométricos, ingesta de alimentos y muestras de sangre. Se realizó prueba de tolerancia a la glucosa (GTT), el perfil de lípidos (PL), la peroxidación de lípidos (TBARS) y la cuantificación de carbonilos en proteínas oxidadas como pruebas de bioquímica sanguínea. GTT y PL no fueron diferentes entre ambos grupos en la evaluación de seguimiento de 15 y 30 días del consumo de la barra. No hubo diferencias significativas en los TBARS o la concentración de carbonilo entre los grupos, el grupo BFB mostró niveles más altos de peroxidación de lípidos en suero en la fase basal y a los quince días del consumo de la barra; curiosamente, estos niveles disminuyeron en la evaluación final. No se detectaron diferencias en los niveles de carbonilo entre los grupos. En conclusión, 30 días de consumo de barras de fibra de frijol no alteraron los niveles de glucosa o PL; mientras que, en el grupo BFB, el estrés oxidativo disminuyó a los 30 días del consumo de la barra fortificada.